Kemitraan Asosiasi Profesi Kesehatan dalam Aplikasi Metode KESET untuk Menangani Stress di Masa Pandemi Covid-19 bagi Masyarakat Desa Cibiru Wetan dan Praktisi Apoteker Kabupaten Sumedang, Jawa Barat - Aiyi Asnawi; Widhya Aligita; Soni Muhsinin; Nur Intan Hayati Husnul Khotimah; Eki Pratidina; Iceu Mulyati; Yulianti Anjayani; Ellin Febrina; Fauzan Z Muttaqin (Universitas Mathla'ul Anwar Banten, 2021)
PARTNERSHIP OF THE HEALTH PROFESSIONAL ASSOCIATION IN THE APPLICATION OF THE KESET METHOD TO MANAGE STRESS DURING THE COVID-19 PANDEMIC FOR THE PEOPLE OF CIBIRU WETAN VILLAGE AND PHARMACIST PRACTITIONERS IN SUMEDANG REGENCY, WEST JAVA. EFT (Emotional Freedom Technique) is an alternative treatment method that offers healing from physical and emotional pain and disease. EFT works by tapping on acupressure meridians to release blockages. When these blockages are released, the problem feeling can be released and move through the body. Learning EFT also empowers the client to take charge of handling their emotional state/ controls stress. because they can tap on a feeling any time, they want to move out a painful feeling. Impact of quarantine or PSBB, the restriction of movement of people, is the mental health toll became even steeper including for community of Desa Cibiru Wetan and pharmacist of Kabupaten Sumedang, West Java. Therefore, the purpose of this community service activity was to transfer knowledge about the EFT method for stress management during the Covid-19 pandemic for the Desa Cibiru Wetan community and pharmacist in Kabupaten Sumedang, West Java. The stages of this activity began from education about stress and its prevention, and continues with the introduction of the KESET method in managing stress independently. The critical point in this activity is how to transfer knowledge and skills in preparing the participants who use this technique believe tapping the body can create a balance in their energy system and treat pain. The results of the activity showed that community participation could improve the knowledge and ability of participants in handling their emotional state/ controls stress by using KESET method. In conclusion, this activity could be an alternative healing from emotional pain for participants.